Al-Quran dan Astronomi - Sofyan Sauri (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Astronomy is a branch of science that has been researched by Muslim scientists and western scientists. Al-Khwarizmi emphasized that astronomy (annujum at-tanjim) is a science that studies theoretically celestial bodies such as stars, planets, and the zodiacs. From here, astronomy becomes an effective tool for understanding the nature of celestial bodies. In order to gain useful knowledge from celestial bodies, the Qur'an often associates the times of worship with universal phenomena, especially the moon and the sun. Based on this phenomenon, it is necessary to research the astronomical perspective in the Qur'an. This type of research is qualitative, the research methodology used is library research. In this paper the author tries to reveal much deeper about Astronomy from the perspective of the Koran, and uncovers astronomical verses.